O relaxamento como terapia complementar em portadores de hanseníase e seu efeito na percepção da dor e na variabilidade da frequência cardíaca - Fernandes, Gislaine Buzzini (2015)
Pain is an important complaint of leprosy patients. This study aimed to evaluate the effect of relaxation in the treatment of pain in leprosy and the impact of this approach on pain perception and heart rate variability (HRV). Methods: This quantitative, analytical study employed three instruments for data collection. Twenty leprosy patients were enrolled in the Núcleo de Gestão Assistencial 60 Clinic in São José do Rio Preto, SP. The modified Jacobson Progressive Muscle Relaxation technique was used together with coordinated breathing exercises to achieve the desired level of relaxation of different muscle groups. A Polar ® Advanced S810i device (transmitter belt with timer) was worn by one selected participant in each relaxation session .A questionnaire and visual analogue scale were used to quantify pain. Further more practical training meetings were held to apply the relaxation technique. The Kubios_HRV computer program was used to calculate variables, and the Stats Direct 2-6-3 program for descriptive and inferential analysis. Data are reported as means, standard deviation, median and quartiles. The paired two-tailed Student t-test and Wilcoxon test were used for statistical analysis. An alpha error of 5% (p-value ≤ 0.05) was considered acceptable. Results: Statistically significant improvement (p-value=0.0064) in the degree of perceived pain was reported within the first five relaxation sessions. Further tests showed significant improvements after five and ten sessions of relaxation as patients felt less pain proving the efficacy of the relaxation technique. The results of the effects on heart rate variability identified statistically significant improvements with relaxation exercises in respect to time domain variables (SDNN, RMSSD and pNN50), frequency domain (LF, HF and LF/HF) and non-linear domain (SD1, SD2 and SD1/SD2). This demonstrates that this procedure improves over all autonomic behavior since improved variability is associated with a better homeostatic condition. Conclusions: Therapeutic exercises can be considered an important resource to improve and prevent disabilities in individuals with pain due to leprosy.